2022
DOI: 10.1021/acs.energyfuels.2c00994
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Photoanode Material for Photoelectrochemical Water Splitting: A Review of Bismuth Vanadate

Abstract: Photoelectrochemical (PEC) technology for water splitting has been regarded as one of the most appealing and environmentally friendly approaches to converting light energy into hydrogen energy. The semiconductor material used as the photoelectrode is considered to be the most important factor affecting the efficiency of the PEC system. Bismuth vanadate (BiVO 4 ), as a n-type semiconductor material, has a wide light absorption range, strong catalytic ability, high stability, and low cost, which makes it one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 138 publications
0
21
0
Order By: Relevance
“…The photoelectrochemical (PEC) water splitting is considered one of the most promising H 2 generation methods with required potential (DG °= 237 kJ mol −1 ), due to its use of the unlimited energy source of solar light without producing any CO 2 . [2][3][4][5] Since 1972, aer the pioneering work by Fujishima and Honda using TiO 2 as a photocatalyst in a water splitting system. 6 To achieve high performance of PEC materials, suitable band gap, diffusion length, bulk defects and surface recombination, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The photoelectrochemical (PEC) water splitting is considered one of the most promising H 2 generation methods with required potential (DG °= 237 kJ mol −1 ), due to its use of the unlimited energy source of solar light without producing any CO 2 . [2][3][4][5] Since 1972, aer the pioneering work by Fujishima and Honda using TiO 2 as a photocatalyst in a water splitting system. 6 To achieve high performance of PEC materials, suitable band gap, diffusion length, bulk defects and surface recombination, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Du’s group published a minireview on the role of co-catalysts on BiVO 4 photoanodes for photoelectrochemical water oxidation . Liu et al reviewed bismuth vanadate as visible light photoanode materials for photoelectrochemical water splitting . Yi and co-authors presented an enhanced self-biased photoelectric performance of BiVO 4 driven by the anomalous photovoltaic effect induced by applying unidirectional mechanical polishing .…”
Section: Photoelectrocatalysismentioning
confidence: 99%
“…41 Liu et al reviewed bismuth vanadate as visible light photoanode materials for photoelectrochemical water splitting. 42 Yi and co-authors presented an enhanced selfbiased photoelectric performance of BiVO 4 driven by the anomalous photovoltaic effect induced by applying unidirectional mechanical polishing. 43 Ng's group reported that an improved charge transportation area between WO 3 and Bi 2 WO 6 photoanodes promoted the improvement in the photoelectrochemical performance.…”
Section: ■ Photooxidationmentioning
confidence: 99%
“…33 The modified BiVO 4 has high photocurrent and stability, which makes it a potential PEC photocatalytic electrode material. Shi et al summarized the BiVO 4 electrode from preparation methods and different modification methods, 34 and Wang et al 35 have summarized the methods of introducing an oxygen vacancy and the effect of oxygen vacancy on the PEC water splitting of BiVO 4 photoanodes. Furthermore, Gaikwad 36 overviewed the bulk, surface, and interface engineering methods on BiVO 4 photoanode such as doping, defect engineering, and nanostructuring to enhance the PEC performance.…”
Section: Introductionmentioning
confidence: 99%